Death Row Narratives: A Qualitative Analysis of Mental Health Issues Found In Death Row Inmate Blog Entries - Johnson, Robert (The prison journal, 2021)
Death row inmate narratives, culled from online blogs, are used to explore the social determinants of mental health in the context of the stresses and deprivations of living on death row. Legal and correctional procedures that affect death row inmates are conceptualized as social determinants of mental health. These procedures include the granting or denying of stays of execution, conditions of solitary confinement during death row and the death watch, and impending dates of execution. Death row narratives offer a nuanced account of the many ways condemned prisoners must contend with their powerlessness as an essential element of life under sentence of death.